2011
DOI: 10.1007/s00134-011-2442-7
|View full text |Cite
|
Sign up to set email alerts
|

Xenon offers stable haemodynamics independent of induced hypothermia after hypoxia–ischaemia in newborn pigs

Abstract: Xe maintained stable blood pressure, thereby reducing the inotropic support requirements during and after administration independently of induced HT-current neonatal encephalopathy treatment. Xe may offer haemodynamic benefits in clinical neuroprotection studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…The mean HR decreased by 60 bpm during SHC equating to 17 bpm/°C using T deep brain or 40 bpm/°C using T rectal , and we previously reported that HT reduces HR by around 10 bpm/°C. This suggests that brain temperature is a more important determinant for HR than body temperature, consistent with the temperature-sensing area being in the hypothalamus (34).…”
Section: Cardiovascular Effectssupporting
confidence: 52%
“…The mean HR decreased by 60 bpm during SHC equating to 17 bpm/°C using T deep brain or 40 bpm/°C using T rectal , and we previously reported that HT reduces HR by around 10 bpm/°C. This suggests that brain temperature is a more important determinant for HR than body temperature, consistent with the temperature-sensing area being in the hypothalamus (34).…”
Section: Cardiovascular Effectssupporting
confidence: 52%
“…22 Xe + TH improved cardiovascular stability and reduced inotropic requirements. 23 There was no increased oxygen requirement, no cuffed tracheal tube complications, and no stridor or extubation delays in either our experimental pig study 12 (n = 120) or this clinical study. There are ongoing concerns regarding neuroapoptosis in the immature brain with inhalation anesthetic agents.…”
mentioning
confidence: 64%
“…23,24 The physiological decrease in HR during TH was counteracted by inotropic support in neonates, similar to previous findings in pigs. 25 The mean arterial blood pressure level for infants during TH did not differ between the infants with and without inotropic support, and it seems as clinicians aim for the same blood pressure at the two temperatures. 22 However, the optimal mean arterial blood pressure during TH is yet to be defined.…”
mentioning
confidence: 82%